World Bank East Asia and Pacific Economic Update, October 2017 : Balancing Act - World Bank (Washington, DC: World Bank, 2017)
The economic outlook for the developing EAP region remains positive, and will benefit from an improved external environment as well as strong domestic demand. The growth of regional GDP excluding China is forecast to accelerate in 2018, while China's GDP growth is expected to decline in 2018 and 2019, although remain higher than most countries in the region. Poverty is projected to continue its long-term decline. Major downside risks include financial sector vulnerabilities, large fiscal imbalances, and the possible escalation of geopolitical tensions. The improved outlook for global growth provides a window of opportunity for developing EAP to continue to reduce key vulnerabilities and strengthen the foundations for sustained and inclusive growth in the medium term. The region could also benefit from further developing tourism sectors and deepening of regional integration, to offset the emerging global protectionism. And policies to ensure inclusive growth should involve ensuring economic mobility and security for all, going beyond the primary focus on reducing poverty.